Desain konsep kendaraan roadster tahun 2050 yang menerapkan teknologi turbine engine - Geggy Gamal Surya; Khaola Rachma Adzima (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2019)
The design in the next 30 to 100 years is a vision of industrial desainers to be able to provide an overview or exposure to the government, companies, industry players and the public, how this future product is projected (pictured) into a mature mind and can be realized according to provisions in his time. This depiction needs to be exploited through design education science. Without the knowledge of design education, thinking in this design cannot be described. Describe what is meant is "design process". Methods Research in the concept vehicle design uses qualitative methods and uses analysis and design that includes background, issue, problem solving, purpose and benefits of design, concept design, image board, image chart, mood board, keyvisual, keyword, brainstorming sketches, developing sketches, detailing sketches, final sketches, Computer Aided Industrial Design (3D Design), and final 3D. Conclusions from the results of designing future vehicle concepts can be continued as a result of further research in the role of scientific design in industrial design and transportation. The ability of Indonesian desainers, especially in the field of industry and transportation, has been able to move internationally as desainers of international-level vehicles. Key words: transportation design, vehicle design, vehicle concept